First records of the Oak bush-cricket Meconema thalassinum on three German North Sea islands (Orthoptera: Ensifera, Tettigoniidae) - Ahnelt, Harald; Pleitner, Sara; Schulz, Björn (Fragmenta entomologica, 2021)
We provide the first records of the Oak bush-cricket Meconema thalassinum on the three German North Sea geest islands Amrum, Föhr and Sylt, based on monitoring and citizen science. The presence of the Oak bush-cricket on these German islands is probably due to unintentional introduction.